Pressure control using sliding modes for the expiratory cycle in mechanical ventilation systems - Riva, Diego A. (2023)
Mechanical ventilation (MV) is crucial in the recovery of patients with severe respiratory failure. The expiratory phase, in particular, presents specific dynamic complexities. In this context, control systems represent fundamental components for the adequate performance of MV systems. However, traditional control approaches employed in the literature have limitations in addressing these complexities and ensuring accurate performance. This article addresses the challenges associated with controlling the expiratory stage in MV systems through a robust and effective solution based on sliding mode control. In particular, the proposed control approach in this article is based on a non-linear model recently validated in the literature. Thus, the objective is to overcome the limitations of traditional approaches and provide a robust and efficient control solution that overcomes the solutions available in the literature. The results show the potential of this control strategy in real clinical settings. The sliding mode control approach improves the performance and convergence of MV systems, contributing to more effective ventilation therapy and better patient recovery.